Aktivitas Antioksidan Daun Sirsak (Annona muricate L.): A Systematic Review - Rahayu, Rinoa Sahda; Wulandari, Cyntia (Journal Syifa Sciences and Clinical Research (JSSCR), 2025)
Antioxidants are compounds that can ward off free radicals that can affect health. This study aims to identify antioxidant compounds in soursop leaves through a literature review writing method with reference to PRISMA. Which was conducted between 12 and 14 December 2024 online through Dimension with the keywords "soursop leaves"; OR/AND "antioxidants". According to the findings of this review, three journals were identified that discuss the antioxidant activity of soursop leaves (Annona muricata L.) using the DPPH method, as indicated by the IC50 results. There were 3 articles that were included in the selection and the results showed that soursop leaves are used as a source of natural antioxidants that are effective in fighting free radicals.